Poly (meth) acrylate impact modifiers with reduced metal ion content and methods for production thereof
By reducing the amount of alkali metal ions in the impact modifier and adopting ion exchange and coagulation techniques, the problem of the reduction in transparency of the impact-modified PMMA molding composition after hot water storage is solved, achieving high transparency and high transmission rate effect.
Patent Information
- Application Number
- CN202380036847.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2023-04-25
- Publication Date
- 2025-01-10
AI Technical Summary
The existing impact-modified PMMA molding compositions have reduced transparency after hot water storage, exhibiting creamy white and high haze, making it difficult to meet the requirements of high transparency and high transmittance.
By reducing the amount of cationic metal ions, especially the total amount of alkali metal ions, to 4.5 mmol/kg or less in the impact modifier, the cation exchange material and anion exchange material are used to combine physical aggregation and Mechanical dehydration, prepare a heterogeneous (meth)acrylate emulsion polymer, reduce the content of alkali metal ions to improve the storage stability of hot water.
The haze after hot water storage is significantly reduced and the light transmittance is maintained, ensuring high transparency performance of impact modifiers and molding compositions under hot water conditions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to poly(meth)acrylate impact modifiers comprising at least one multiphase alkyl(meth)acrylate emulsion polymer having a defined low cationic content, in particular a very low concentration of alkali metal ions, such as sodium. The impact modifiers according to the invention and the molding compositions produced therefrom have improved optical properties, in particular high transparency after hot water storage.
[0002] Furthermore, the present invention relates to a process for producing a poly(meth)acrylate impact modifier, which comprises preparing at least one multiphase alkyl(meth)acrylate polymer by emulsion polymerization, followed by an ion exchange step of the resulting latex, for example using cation and / or anion exchanger materials, combined with coagulation and mechanical dehydration, wherein the amount of cationic metal ions, such as alkali metal ions, in the dehydrated alkyl(meth)acrylate emulsion polymer is reduced.
[0003] The invention also relates to impact-modified molding compositions, in particular impact-modified poly(methyl methacrylate) (PMMA) compositions, having an improved combination of properties, including good optical properties, in particular high transparency after hot water storage. The molding compositions are preferably used for producing molded articles and semi-finished products, such as films and sheets, in particular transparent articles and semi-finished products or products with good optical appearance. Background Art
[0004] It is known that the so-called impact modifier can be used to improve the impact resistance of molding compositions, especially relatively brittle synthetic resins, such as poly (meth) acrylate molding compositions, by mixing an appropriate amount. The impact modifiers that are called core particles, core-shell particles or core-shell-shell particles made by emulsion polymerization have become industry practice. These usually include an elastomeric phase (for example as a core or as an intermediate shell grafted onto the core) and a hard outer phase (which usually ensures that the impact modifier particles are well incorporated into the matrix polymer). Such multiphase emulsion polymers and their preparation are for example described in WO 2004 / 056893.
[0005] Typically, such impact modifiers made by emulsion graft polymerization are obtained as aqueous polymer dispersions (latexes), which require post-treatment by coagulation and separation of the emulsion polymer.Several coagulation (also called precipitation) processes of polymer latexes are known and described in the prior art.
[0006] For example, it is described that emulsion polymers, such as the poly(meth)acrylate impact modifiers of the present invention, can be coagulated by means of known physical coagulation methods, such as shear coagulation, hot shear coagulation, spray drying, freeze coagulation or pressure coagulation methods, or by means of chemical coagulation methods, which include the addition of electrolytes, in particular polyvalent cations, such as alkaline earth metal salts, aluminum salts or zinc salts, or inorganic or organic acids.
[0007] For example, WO 2015 / 074883 describes the coagulation of aqueous polymer dispersions by means of continuous or semi-continuous freezing coagulation and subsequent mechanical dewatering (for example using a centrifugation step). For example, WO 2002 / 184539, EP 0 683 028 and EP 0 187 715 describe the coagulation and dewatering of emulsion polymers via thermal shear coagulation in extruder lines.
[0008] Another common way for the coagulation of emulsion polymers is to mix the emulsion polymer (latex) with a coagulant, which is often selected from aqueous solutions of metal salts (especially divalent or trivalent metal ions) and / or acids (such as sulfuric acid, acetic acid, phosphorous acid). For example, aqueous solutions of alkali metal salts, alkaline earth metal salts, zinc salts or aluminum salts, such as magnesium sulfate, calcium chloride and aluminum chloride, are used as coagulants.
[0009] Document EP 2 942 360 describes a thermoplastic resin powder obtained by coagulating a polymer latex made by emulsion polymerization using a phosphoric acid ester as an emulsifier, wherein the free acid content in the resin is not more than 500 ppm. For example, aluminum sulfate or sulfuric acid is used as a coagulant. EP 2 942 360 describes that the presence of polyvalent metal ions in the thermoplastic resin powder leads to a reduction in the fluidity of the thermoplastic resin powder, so the amount of coagulant should be as small as possible. It is described that the thermoplastic resin powder contains less than 50 ppm of calcium, preferably less than 50 ppm of calcium and magnesium combined, and 60 to 300 ppm of aluminum and more than 50 ppm of phosphorus. The amount of alkali metal ions is not discussed in EP 2 942 360.
[0010] Document GB 2 226 324 A describes a transparent, viscous molding composition comprising 10 to 90% of a hard phase made of methyl methacrylate and 1 to 90% of a viscous phase, for example made of a crosslinked butyl acrylate polymer, distributed in the hard phase, wherein the molding composition contains not more than 0.05% by weight of water-soluble components. It is described that the aqueous phase is separated from the coagulant in liquid form to such an extent that not more than 0.05% by weight of water-soluble components remain in the composition in order to ensure permanent clarity, in particular under the action of moisture.
[0011] Document US 2021 / 054113 A1 describes a multilayer acrylic polymer coacervate characterized by its bulk density, particle diameter, wherein the amount N (in mmol / kg) of alkali metal and alkaline earth metal is defined by the formula ∑(N / a) *(120-Tg) ≤ 100 based on the glass transition temperature Tg (in °C) of the acetone solubles of the coacervate and the valence a of the alkali metal and alkaline earth metal. The multilayer acrylic polymer coacervate of D1 is said to exhibit excellent transparency, hot water whitening resistance and stress whitening resistance.
[0012] Document KR 2018 0069421 A describes an impact modifier capable of imparting impact strength to epoxy resins and a method for preparing the same, wherein the content of residual emulsifiers and metal ions is reduced, and coagulation is achieved by adding hydrochloric acid and lowering the pH to below 3. The content of metal ions should be reduced to a level below 90 ppm by a post-treatment step. The impact modifier described in KR 2018 0069421 A contains a specific polyalkylene glycol-based comonomer, such as polyethylene glycol methacrylate (PEGMA). In addition, a specific phosphate-based emulsifier is used in the method for preparing the impact modifier.
[0013] Furthermore, it is described in the prior art to subject polymer latexes, for example fluoropolymer latexes, to an ion exchange step, for example in order to reduce the metal ion content in the polymer latex.
[0014] DE 2 046 220 A describes the separation of polydisperse particle dispersions by size by passing the polydisperse particle dispersion through a bed of solid particles that are larger than the particles to be separated and eluting the bed with a dispersion medium to remove particles from the bed according to particle size. The bed of solid particles can be a bed of glass beads or crosslinked polystyrene beads. Ion exchanger materials are also used in this context.
[0015] EP 0 591 888 A1 describes a method for the post-treatment of aqueous dispersions of fluorinated thermoplastics, which comprises substantially replacing cations in the aqueous dispersion with hydrogen ions, compressing the dispersion (optionally after dilution with water) and coagulating the dispersion by unloading the dispersion through a small opening. Optionally, the coagulated dispersion is filtered, washed, mechanically dewatered, broken into a free-flowing product and dried. The technical teaching of EP 0 591 888 A1 is concerned with the continuous post-treatment of aqueous dispersions of fluorinated thermoplastics at high throughput, without taking into account optical properties.
[0016] EP 0 571 069 A2 discloses a method for improving the water whitening resistance of a pressure-sensitive adhesive by removing water-soluble ions and adjusting the pH of the pressure-sensitive adhesive formulation to at least about 6.0. Deionized adhesives that are not readjusted to a pH greater than about 6.0 do not show improved water whitening resistance. Water-soluble ions are removed by contacting an aqueous latex or adhesive formulation with an ion exchange resin, wherein preferably cations (e.g., with sulfonic acid cation exchangers) and anions (e.g., using quaternary ammonium anion exchange resins), such as so-called mixed bed ion exchangers, should be removed. The amount of cations and anions in the pressure-sensitive adhesive is not mentioned in EP 0 571 069 A2.
[0017] WO 2001 / 57100 A1 describes the preparation of ultra-clean, i.e. salt-free, fluoropolymers by aqueous emulsion polymerization, removing substantially all ions other than NH4+, H+ and OH-, and coagulating the fluoropolymers without adding ions. For applications such as curable compounds and coatings, the focus is on avoiding metal-free acid acceptors, i.e. strong organic bases. Optical properties are not considered.
[0018] WO 2013 / 160029 describes a polymer composition containing at least a graft polymer made by emulsion polymerization and optionally a thermoplastic polymer, a rubber-free vinyl (co)polymer and other polymers or polymer additives. The emulsion graft copolymer is precipitated with at least one alkaline earth metal salt in an alkaline medium, and the copolymer comprises at least one sodium salt and at least one alkaline earth metal salt in a molar ratio Na / (Mg+Ca) of at least 0.10 and at most 1.0. It is described that the molded articles prepared from the emulsion graft copolymer show improved surface quality after storage under warm-humidity conditions. In contrast to the present invention, it is suggested to increase the amount of sodium by adding a sodium salt during the emulsion polymerization and / or coagulation process.
[0019] Particularly important properties of impact-modified PMMA molding compositions are favorable mechanical properties, such as high toughness (impact resistance, notched impact resistance), high elasticity (elastic modulus) as well as good processability (thermoplastic flowability, MVR) and good weathering and heat resistance. In addition, a fundamental requirement for PMMA molding compositions and articles is optical transparency even at elevated temperatures or after exposure to hot water. Generally, optically transparent products are those having a haze value of less than or equal to 15.0%, in particular below 10.0%, very particularly below 6.0%, measured at 23° C. on a specimen with a thickness of 1 mm according to standard ASTM D1003 (2013) with the aid of a BYK GardnerHazegard-plus haze meter.
[0020] Generally, the problem is that impact-modified PMMA molding compositions and articles made therefrom exhibit reduced transparency and become milky after storage in hot water, in particular in water at 80° C. for 10 to 24 hours. Therefore, it is highly desirable to provide impact-modified PMMA molding compositions that exhibit reduced haze and high light transmittance after storage in hot water. Summary of the invention
[0021] Purpose of the Invention
[0022] It is an object of the present invention to provide poly(meth)acrylate impact modifiers, and molding compositions, moldings and semi-finished products, such as films and sheets, comprising the poly(meth)acrylate impact modifiers, which have improved optical properties, in particular high transparency and high transmittance. In particular, the impact modifiers should lead to lower haze values according to ASTM D 100-13 compared to prior art modifiers, in particular after hot water storage at 70° C. to 80° C. In addition, the impact modifiers should also exhibit high transmittance values even after hot water storage at 70° C. to 80° C., for example for 4 to 24 hours. In particular, it is an object of the present invention to provide an impact modifier or a semi-finished product, preferably a transparent semi-finished product, which after hot water storage at 70° C., preferably at 80° C., for example after 4 to 24 hours, has a haze measured according to standard ASTM D1003 (2013) at 23° C. on a test specimen with a thickness of 1 mm of ≤ 40%; preferably ≤ 30%, preferably ≤ 20%.
[0023] Another object of the present invention is to provide a cost-effective and easy process for producing improved poly(meth)acrylate impact modifiers and / or impact-modified polymer compositions. Solution according to the invention
[0024] Surprisingly, it has been found that the haze of an impact modifier or a transparent article made therefrom after hot water storage is negatively affected by the presence of ionic species, in particular alkali metal ions. It has been found that if the total amount of cationic metal ions, in particular alkali metal ions, in the impact modifier, in particular after coagulation and dehydration, is reduced to or below a critical value of about 4.5 mmol / kg, preferably 3.0 mmol / kg, more preferably 1.0 mmol / kg, based on dry impact modifier, the haze after hot water storage is reduced. Furthermore, in general, the impact modifiers of the present invention and samples comprising the same exhibit high transmittance values even after hot water storage.
[0025] Preferably, the reduction of ionic species, in particular alkali metal ions, can be carried out by an ion exchange step. In addition, it is possible to reduce the amount of metal ions, in particular alkali metal ions, by known washing, dilution and / or dehydration steps. It has surprisingly been found that a defined amount of alkaline earth metal salt can be added as a coagulant after the ion exchange step to assist coagulation without impairing the haze after hot water storage.
[0026] Typically, the cationic metal ions, such as alkali metal ions or polyvalent metal ions (e.g., alkaline earth metals, zinc and aluminum) are from additives used in emulsion polymerization, such as emulsifiers, initiators and buffers. Typically, the content of ionic species in the polymer of the coagulation can be reduced by washing and / or by a higher degree of dehydration. However, this washing process consumes time and cost, and produces a large amount of wash water. Here, surprisingly, it is found that, by an ion exchange step, for example, using a cation exchange material (usually including an acidic group, such as a sulfonic acid group) and an optional anion exchanger material (usually including a basic group, such as a quaternary ammonium group), it is easy and advantageous to obtain such a required low amount of cationic metal ions, particularly alkali metal ions. It has been found that the polymer latex of the multiphase (meth) alkyl acrylate polymer obtained after emulsion polymerization remains stable and does not show coagulation during this ion exchange step. Therefore, if an additional ion exchange step is carried out before coagulation, the hot water storage stability of the impact modifier or its composition can be improved.
[0027] Description of the invention
[0028] The present invention relates to a poly(meth)acrylate impact modifier (hereinafter also referred to as impact modifier), which comprises (preferably essentially consists of) at least one multiphase alkyl(meth)acrylate emulsion polymer (hereinafter also referred to as emulsion polymer), wherein the total amount of alkali metal ions, preferably sodium and / or potassium, in the impact modifier is less than or equal to 4.5 mmol / kg, preferably less than or equal to 3.0 mmol / kg, more preferably less than or equal to 2.0 mmol / kg, based on the solid content of the impact modifier.
[0029] In a preferred embodiment, the poly(meth)acrylate impact modifier comprises less than or equal to 1.0 mmol / kg, preferably less than or equal to 0.9 mmol / kg, more preferably less than or equal to 0.5 mmol / kg of alkali metal ions, preferably sodium and / or potassium, based on the solids content of the impact modifier.
[0030] More preferably, the poly(meth)acrylate impact modifier comprises 0 to 4.5 mmol / kg, preferably 0 to 3.0 mmol / kg, more preferably 0 to 1.0 mmol / kg, preferably 0.01 to 4.5 mmol / kg, further preferably 0.01 to 3.0 mmol / kg, further preferably 0.01 to 1.0 mmol / kg of alkali metal ions, based on the solids content of the impact modifier.
[0031] Preferably, the poly(meth)acrylate impact modifier of the present invention contains less than or equal to 20.0 mmol / kg, preferably less than or equal to 10.0 mmol / kg, more preferably less than or equal to 9.0 mmol / kg of cationic metal ions (i.e., the sum of all cationic metal ions, such as alkali metal ions and multivalent ions, such as alkaline earth metal ions, aluminum ions and / or zinc ions), based on the solid content of the impact modifier. Typically, the total amount of cationic metal ions (e.g., alkali metal ions, alkaline earth metal ions, aluminum ions and / or zinc ions) is in the range of 0.1 to 20.0 mmol / kg, preferably 0.4 to 10.0 mmol / kg.
[0032] Preferably, the poly(meth)acrylate impact modifier of the present invention contains less than or equal to 6.5 mmol / kg of sulfur (calculated as sulfate), preferably less than or equal to 5.0 mmol / kg, more preferably less than or equal to 6.5 mmol / kg, based on the solid content of the impact modifier. Typically, the impact modifier contains less than or equal to 6.5 mmol / kg, preferably less than or equal to 5.0 mmol / kg of sulfur-containing anions (calculated as sulfate), based on the solid content of the impact modifier.
[0033] Typically, the metal ions (e.g., alkali metal ions and / or polyvalent metal ions selected from alkaline earth metals, zinc and aluminum) contained in the impact modifier of the present invention come from the auxiliaries used in the emulsion polymerization process of the multiphase (meth) alkyl acrylate emulsion polymer, such as initiators, surfactants and buffer salts. In addition, the metal ions may come from additives added to the impact modifier, such as stabilizers. In particular, the alkali metal ions contained in the impact modifier of the present invention come from the initiator and / or surfactant used in the emulsion polymerization.
[0034] Typically, a significant amount of metal ions in the impact modifier may come from the coagulant used to separate the emulsion polymer from the aqueous latex dispersion. Therefore, the multiphase alkyl (meth)acrylate emulsion polymer of the impact modifier of the present invention is preferably coagulated without the addition of a coagulant, such as a metal salt. Typically, coagulation is performed by means of physical coagulation. In addition, it is possible to perform coagulation by means of physical coagulation with the addition of at least one coagulant selected from polyvalent metal ions, such as calcium salts, magnesium salts and / or aluminum salts.
[0035] According to a preferred embodiment, the coagulation of the multiphase alkyl (meth)acrylate emulsion polymer is carried out by means of physical coagulation without the addition of a coagulant, for example a coagulant selected from polyvalent metal ions. For example, the poly(meth)acrylate impact modifier comprises less than or equal to 4.5 mmol / kg, preferably less than or equal to 3.0 mmol / kg, more preferably less than or equal to 2.0 mmol / kg, and also preferably less than or equal to 1.0 mmol / kg of cationic metal ions (i.e. the sum of all cationic metal ions, for example alkali metal ions and polyvalent ions, such as alkaline earth metal ions), based on the solid content of the impact modifier. For example, the poly(meth)acrylate impact modifier may contain sodium ions and / or potassium ions, and the amount of all other cationic metal ions is below the detection limit of the respective analytical method.
[0036] According to another preferred embodiment, at least one polyvalent metal salt (e.g. alkaline earth metal salt, aluminum salt and / or zinc salt) is added as a coagulant and the poly(meth)acrylate impact modifier comprises less than 4.5 mmol / kg, preferably less than 3.0 mmol / kg, more preferably less than 1.0 mmol / kg of the sum of alkali metal ions, based on the solids content of the impact modifier, and 0.4 to 15.0 mmol / kg, preferably 0.5 to 10.0 mmol / kg of polyvalent metal ions (e.g. alkaline earth metal ions, aluminum ions and / or zinc ions), based on the solids content of the impact modifier.
[0037] The term "polyvalent metal" or "polyvalent metal ion" relates to a metal ion having two or more, preferably two or three, ionic charges. Preferably, the polyvalent metal ion may be selected from metals of IUPAC Group 2 (alkaline earth metals) and IUPAC Groups 8 to 14, more preferably selected from metals of IUPAC Group 2 (alkaline earth metals), IUPAC Group 12 (zinc group) and IUPAC Group 13 (boron group).
[0038] The term "alkali metal" or "alkali metal ion" includes elements of IUPAC Group 1 of the Periodic Table, in particular lithium (Li), sodium (Na) and potassium (K). The term "alkaline earth metal" or "alkaline earth metal ion" includes elements of IUPAC Group 2 of the Periodic Table, in particular magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba).
[0039] As used herein, the term "(meth)acrylate" is intended to encompass methacrylates, acrylates, and mixtures thereof.
[0040] The term "alkyl (meth)acrylate polymer" refers to a polymer comprising at least 30 wt%, preferably at least 40 wt%, more preferably at least 50 wt% of alkyl (meth)acrylate monomer units, and includes copolymers of alkyl (meth)acrylate monomers and one or more other copolymerizable monomers.
[0041] The term "alkyl (meth)acrylate emulsion polymer" refers to a multiphase emulsion polymer comprising at least 30 wt%, preferably at least 40 wt%, more preferably at least 50 wt% of alkyl (meth)acrylate monomer units in the shell, wherein the shell may include a copolymer of an alkyl (meth)acrylate monomer and one or more other copolymerizable monomers (e.g., styrene).
[0042] The term "aqueous" or "aqueous solution" means that the medium or solvent consists of water or contains water as a major component. For example, a polar water-miscible co-solvent, such as an alcohol, may be included in the medium or solvent.
[0043] The term "latex" as used in connection with the present invention refers to a water-insoluble polymer which is dispersed in an aqueous phase, preferably stabilized by one or more surfactants, and which is prepared by conventional polymerization techniques, preferably by emulsion polymerization.
[0044] If not defined otherwise, according to the present invention, the term ppm refers to ppm based on weight, such as mg / kg. For example, the term ppm refers to mg / kg based on the solid content of the poly(meth)acrylate impact modifier.
[0045] The content of metal ions, such as alkali metals and alkaline earth metals in emulsion polymers or impact modifiers is usually determined by atomic emission spectrometry after chemical digestion of the polymer sample, for example after microwave-assisted digestion of the polymer sample in nitric acid. The amount of alkali metals and polyvalent metals, such as alkaline earth metals or aluminum is given taking into account the typical detection limit of the respective analytical method. For example, an amount given in 0 weight %, 0 ppm or 0 mmol / kg is understood to be below the detection limit of the respective analytical method.
[0046] Preferably, the polyvalent metal ion is selected from metal ions of IUPAC Group 2 (alkaline earth metals), IUPAC Group 12 (zinc group) and IUPAC Group 13 (boron group). More preferably, the polyvalent metal ion is selected from alkaline earth metals, preferably magnesium (Mg) and / or calcium (Ca), and metals of IUPAC Group 13, preferably aluminum. Most preferably, the polyvalent metal ion is selected from alkaline earth metals, zinc (Zn) and aluminum (Al). In a further preferred embodiment, the at least one polyvalent metal ion is selected from magnesium (Mg), calcium (Ca), zinc (Zn) and aluminum (Al), more preferably selected from magnesium (Mg), calcium (Ca) and aluminum (Al).
[0047] In particular, the total amount of cationic metal ions relates to the sum of all metal ions present in the poly(meth)acrylate impact modifier. In particular, the total amount of cationic metal ions comprises alkali metal ions and polyvalent metal ions, such as alkaline earth metal ions and / or aluminum ions. In particular, the amount of alkali metal ions relates to the sum of all alkali metal ions present in the poly(meth)acrylate impact modifier. Preferably, the alkali metal ions are sodium ions and / or potassium ions, and the amount of alkali metal ions relates to the sum of sodium ions and potassium ions.
[0048] Cationic metal ions, such as alkali metal ions, can be present in the impact modifier in any arbitrary form, such as in the form of solid salts or salt inclusions, dissolved in the aqueous phase, bound to or adsorbed to other components or groups of the emulsion polymer, such as anionic groups.
[0049] Typically, the impact modifier comprises or consists essentially of polymer particles prepared by emulsion polymerization. After the emulsion polymerization, the impact modifier is in the form of an aqueous polymer dispersion at the end of the synthesis step. Such an aqueous polymer dispersion is also called latex and contains not only the polymer fraction but also polar water-soluble auxiliary materials added during the polymerization step, such as surfactants, buffer substances, initiators and other redox components.
[0050] Multiphase alkyl (meth)acrylate emulsion polymer
[0051] Preferably, the multiphase alkyl (meth)acrylate emulsion polymer is an emulsion polymer obtained by emulsion polymerization, preferably by sequential emulsion polymerization of alkyl (meth)acrylate monomers and optionally other copolymerizable monomers, wherein the emulsion polymer has a multiphase structure comprising at least one core and at least one, preferably one or two shells.
[0052] For example, multiphase (meth) alkyl acrylate emulsion polymers can be formed by crosslinked particles having a core-shell structure or a core-shell-shell structure. Typically, the average particle diameter of the particles is between 20 nm and 500 nm, preferably between 50 nm and 450 nm, more preferably between 100 nm and 400 nm, and most preferably between 150 nm and 350 nm. The average particle diameter can be determined by methods known to those skilled in the art, for example by static or dynamic light scattering, such as laser diffraction measurements or photon correlation spectroscopy according to DIN ISO 13321:1996. Typically, the volume average particle diameter can be obtained by light scattering measurements.
[0053] In a preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer comprises a soft elastomeric core and a hard non-elastomeric outer phase prepared by graft emulsion polymerization in the presence of the core. The multiphase alkyl (meth)acrylate emulsion polymer is hereinafter referred to as a core-shell emulsion polymer.
[0054] In another preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer comprises a hard non-elastomeric core; a soft elastomeric intermediate shell, typically made by graft emulsion polymerization in the presence of the core, and a hard non-elastomeric outer shell, typically made by graft emulsion polymerization in the presence of the intermediate core-shell particles. The multiphase alkyl (meth)acrylate emulsion polymer is hereinafter referred to as a core-shell-shell emulsion polymer.
[0055] Preferably, the outer shell of the multiphase emulsion polymer is a hard phase which comprises at least 80% by weight, based on the outer shell, of at least one C1-C6 alkyl methacrylate, preferably at least 80% by weight, based on the outer shell, of methyl methacrylate.
[0056] Preferably, at least 50 wt. %, more preferably at least 55 wt. %, more preferably at least 80 wt. %, of the outer layer, based on the total weight of the emulsion polymer, is covalently bonded to the soft phase, i.e. the soft core of a core-shell emulsion polymer or the intermediate shell of a core-shell-shell emulsion polymer. Typically, the amount of covalently bonded outer layer (grafted polymer) (or also referred to as the degree of grafting) is determined as the amount of acetone insolubles.
[0057] To determine the degree of grafting, remove the water from the emulsion polymer dispersion in a drying oven to obtain the solid content of the pure modifier. 1.5 g of the multiphase emulsion polymer is mixed with 40 g of acetone and stirred at 40 ° C until a turbid solution is obtained (2-3 hours). The insoluble grafted polymer is separated by centrifugation (e.g. 9000 rpm, 2-5 hours) and the clear supernatant is dried to constant weight to obtain the amount of the soluble fraction. The degree of grafting is then calculated using formula (1).
[0058] Grafting degree = 100% - acetone soluble content (1)
[0059] Preferably, the degree of grafting of the emulsion polymer is in the range from 50 to 100%, preferably from 52 to 99% by weight, based on the solids content of the emulsion polymer.
[0060] Preferably, the alkyl (meth)acrylate emulsion polymer comprises at least 60% by weight, preferably at least 75% by weight, based on the total emulsion polymer, of at least one C1-C1 (meth)acrylate. 20 Alkyl esters, more preferably methyl methacrylate and / or n-butyl acrylate.
[0061] Typically, (meth)acrylates include (meth)acrylic acid C1-C10 -alkyl esters, (meth) acrylic acid C2-C 20 -Alkenyl ester, (meth) acrylic acid C6-C 20 Aryl ester, (meth) acrylic acid C6-C 20 Aryl alkyl esters, (meth) acrylic acid C1-C 10 Hydroxyalkyl esters, glycol di(meth)acrylates and multifunctional (meth)acrylates.
[0062] Preferably, the emulsion polymer comprises at least one methacrylic acid C1-C 10 Alkyl esters, which are preferably selected from methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, isooctyl methacrylate and ethylhexyl methacrylate, and cycloalkyl methacrylates, such as cyclohexyl methacrylate.
[0063] Preferably, the emulsion polymer comprises at least one acrylic acid C1-C 10 Alkyl esters which are preferably selected from methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, isooctyl acrylate and ethylhexyl acrylate, and cycloalkyl acrylates such as cyclohexyl acrylate.
[0064] Furthermore, it is possible for the emulsion polymer to comprise at least one conjugated diene, such as butadiene, in particular as a soft core.
[0065] In particular, the multiphase alkyl (meth)acrylate emulsion polymer comprises (preferably consists of):
[0066] At least 10% by weight, preferably at least 20% by weight, preferably from 10 to 70% by weight, of at least one methacrylic acid C1-C 10 , preferably C1-C6 alkyl ester, preferably methyl methacrylate;
[0067] 5 to 80% by weight, preferably 20 to 80% by weight, of at least one acrylic acid C1-C 10 Alkyl ester (preferably n-butyl acrylate) or at least one conjugated diene (preferably butadiene);
[0068] 0 to 2 wt %, preferably 0.1 to 2 wt %, more preferably 0.5 to 1 wt % of at least one crosslinking monomer, preferably a multifunctional (meth)acrylate and / or allyl (meth)acrylate; and
[0069] 0 to 15% by weight, preferably 0.5 to 10% by weight, more preferably 0.5 to 5% by weight, of optional additional monomers, preferably different from the abovementioned monomers, for example vinyl aromatic monomers, such as styrene, α-methylstyrene or benzyl methacrylate, preferably styrene.
[0070] More particularly, the multiphase alkyl (meth)acrylate emulsion polymer comprises (preferably consists of):
[0071] At least 40% by weight, preferably 40 to 70% by weight, of at least one methacrylic acid C1-C 10 , preferably C1-C6 alkyl ester, preferably methyl methacrylate;
[0072] 5 to 45% by weight, preferably 20 to 45% by weight, preferably 25 to 42% by weight of at least one acrylic acid C1-C 10 Alkyl ester, preferably C1-C6 alkyl acrylate, preferably selected from ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate and butyl methacrylate, more preferably, C1-C6 alkyl acrylate 10 Alkyl esters include n-butyl acrylate;
[0073] 0 to 2 wt %, preferably 0.1 to 2 wt %, more preferably 0.5 to 1 wt % of at least one crosslinking monomer, preferably a multifunctional (meth)acrylate and / or allyl (meth)acrylate; and
[0074] 0 to 15 wt. %, preferably 0 to 12 wt. %, more preferably 0.5 to 10 wt. % of optional additional monomers, preferably different from the abovementioned monomers, for example vinyl aromatic monomers, for example styrene, benzyl methacrylate.
[0075] The amounts are given based on the total mass of the monomers.
[0076] Preferably, the multiphase alkyl (meth)acrylate emulsion polymer comprises vinyl aromatic monomers such as styrene and / or C7-C8 (meth)acrylate. 20 Arylalkyl esters, such as benzyl methacrylate, are used to adjust the refractive index difference between the hard phase and the soft phase. Styrenes that can be used are styrene, substituted styrenes having alkyl substituents in the side chains, such as α-methylstyrene and α-ethylstyrene, substituted styrenes having alkyl substituents on the rings, such as vinyltoluene and p-methylstyrene, and halogenated styrenes, such as monochlorostyrene, dichlorostyrene, tribromostyrene, and tetrabromostyrene.
[0077] Typically, the crosslinking monomer has two or more polymerizable double bonds in the molecule. The crosslinking monomer may be selected from difunctional (meth)acrylates, trifunctional or polyfunctional (meth)acrylates and other known crosslinking agents such as allyl methacrylate, allyl acrylate and divinylbenzene.
[0078] For example, difunctional (meth)acrylates are diesters of (meth)acrylic acid and polyfunctional alcohols, such as di(meth)acrylates of propylene glycol, butylene glycol, hexylene glycol, octanediol, nonanediol, decanediol, eicosandiol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dodecaethylene glycol, tetradecaethylene glycol, propylene glycol, dipropylene glycol, tetradecapropylene glycol. For example, trifunctional or polyfunctional (meth)acrylates are triesters or polyesters of (meth)acrylic acid and polyfunctional alcohols, such as trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate.
[0079] Suitable crosslinking monomers are described, for example, in WO 02 / 20634 and EP 0 522 351.
[0080] Preferably, the alkyl (meth)acrylate emulsion polymer comprises at least one crosslinking monomer selected from ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, divinylbenzene and allyl (meth)acrylate. More preferably, the crosslinking monomer is allyl methacrylate.
[0081] The alkyl (meth)acrylate emulsion polymer may contain 0 to 15% by weight, preferably 0 to 10% by weight, more preferably 0.5 to 5% by weight, based on the solid content of the emulsion polymer, of additional components, such as auxiliaries or residues of auxiliaries added during polymerization and / or subsequent processing, for example emulsifiers, initiators, buffers or molecular weight regulators as mentioned below. In particular, the alkyl (meth)acrylate emulsion polymer may contain 0 to 15% by weight, preferably 0.001 to 10% by weight, more preferably 0.01 to 5% by weight, based on the solid content of the emulsion polymer, of molecular weight regulators, for example as described below.
[0082] Core-shell emulsion polymer
[0083] For example, the impact modifiers are based on two-phase emulsion polymers consisting of a soft elastomeric core and a hard shell, as described, for example, in EP 0 528 196, DE 38 42 796, DE 10 2005 062 687. In particular, the core-shell emulsion polymers are obtainable by a two-step emulsion polymerization in water, as described, for example, in DE-A 38 42 796. In a first step, the core particles are prepared by emulsion polymerization, and the shell is prepared by emulsion polymerization of a monomer mixture in the presence of the core particles.
[0084] Typically, the hard phase has a glass transition temperature T above 70°C. g The hard phase contains 80 to 100 wt % of methyl methacrylate. Typically, the soft core has a glass transition temperature T of -10°C or less. gand contains 50 to 99.5 wt % of acrylic acid C1-C 10 Alkyl ester and 0.5 to 5 wt % of a crosslinking monomer. In addition, the soft core may have a glass transition temperature T below -10°C. g And may contain 50 to 100 wt % of at least one conjugated diene, such as butadiene, based on the soft core.
[0085] In a preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer is a core-shell emulsion polymer comprising (preferably consisting of):
[0086] A1) 10 to 95% by weight, based on the total emulsion polymer, of a soft elastomeric core A1 having a glass transition temperature T below -10°C g , which is composed of the following substances:
[0087] A1.1) 50 to 99.5% by weight, based on A1, of at least one acrylic acid C1-C 10 Alkyl ester, preferably n-butyl acrylate;
[0088] A1.2) 0.5 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and
[0089] A1.3) 0 to 10% by weight, based on A1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer; and
[0090] B1) 5 to 90% by weight, based on the total emulsion polymer, of a hard shell B1 having a glass transition temperature T above 70° C. g , which is composed of the following substances:
[0091] B1.1) 80 to 100% by weight, based on B1, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate, and
[0092] B1.2) 0 to 20% by weight, based on B1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, selected, for example, from C1-C6-alkyl acrylates, such as butyl acrylate or ethyl acrylate.
[0093] In another preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer is a core-shell emulsion polymer comprising (preferably consisting of):
[0094] A1) 50 to 90% by weight, based on the total emulsion polymer, of a soft elastomeric core A1 having a glass transition temperature T below -10°C g , which is composed of the following substances:
[0095] A1.1) 90 to 100% by weight, based on A1, of at least one conjugated diene, preferably butadiene;
[0096] A1.2) 0 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and
[0097] A1.3) 0 to 10% by weight, based on A1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, for example at least one vinylaromatic monomer, preferably styrene and / or α-methylstyrene; and
[0098] B1) 10 to 50% by weight, based on the total emulsion polymer, of a hard shell B1 having a glass transition temperature T above 70° C. g , which is composed of the following substances:
[0099] B1.1) 70 to 90% by weight, based on B1, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate, and
[0100] B1.2) 10 to 30% by weight, based on B1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, selected, for example, from vinylaromatic monomers, preferably styrene and / or α-methylstyrene.
[0101] Preferably, the degree of grafting of the core-shell emulsion polymer is at least 50% by weight, preferably from 50 to 60% by weight, based on the total solids content of the emulsion polymer.
[0102] Typically, the glass transition temperature T of a polymer or each phase of a multiphase emulsion polymer is g The glass transition temperature T can be determined in a known manner by differential scanning calorimetry (DSC). g It can also be calculated as an approximation using the Fox equation.
[0103] Core-Shell-Shell Emulsion Polymer
[0104] For example, impact modifiers are based on three-phase emulsion polymers, which consist of a hard core, for example of crosslinked methyl methacrylate, a polyol, for example of crosslinked acrylic acid C1-C1 10 The core-shell-shell emulsion polymers are generally prepared as described in EP 1 332 166 B1, WO 02 / 20634 and EP 0 522 351.
[0105] In particular, the poly(alkyl)methacrylate impact modifier may comprise a methacrylate / butadiene / styrene copolymer or an acrylate / methacrylate copolymer.
[0106] In a preferred embodiment, the multiphase alkyl (meth)acrylate emulsion polymer is a core-shell-shell emulsion polymer comprising (preferably consisting of):
[0107] A2) 5 to 40% by weight, based on the total emulsion polymer, of a hard non-elastomeric core A2 having a glass transition temperature T above 50° C. g , which is composed of the following substances:
[0108] A2.1) 80 to 100% by weight, based on A2, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate;
[0109] A2.2) 0 to 20% by weight, based on A2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer; and
[0110] A2.3) 0 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups;
[0111] B2) 20 to 75% by weight, based on the total emulsion polymer, of a soft elastomeric intermediate shell B2 having a glass transition temperature T below 0° C. g , which is composed of the following substances:
[0112] B2.1) 45 to 99.5% by weight, based on B2, of at least one acrylic acid C1-C 10 Alkyl ester, preferably n-butyl acrylate;
[0113] B2.2) 0.5 to 5% by weight, based on B2, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and
[0114] B2.3) 0 to 50% by weight, based on B2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, preferably a monomer having aromatic groups; and
[0115] C2) 15 to 60% by weight, based on the total emulsion polymer, of a hard shell C2 having a glass transition temperature T above 50° C. g , which is composed of the following substances:
[0116] C2.1) 80 to 100% by weight, preferably 90 to 100% by weight, based on C2, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate; and
[0117] C2.2) 0 to 20% by weight, preferably 0 to 10% by weight, based on C2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer.
[0118] Preferably, at least 15% by weight, more preferably at least 25% by weight, of the hard outer shell C2 is covalently bonded to the soft elastomeric middle shell B2.
[0119] Preferably, the degree of grafting of the core-shell-shell emulsion polymer is at least 50% by weight, preferably from 70 to 99% by weight, based on the total solids content of the emulsion polymer.
[0120] Production method of poly(meth)acrylate impact modifier
[0121] Furthermore, the present invention relates to a process for producing a poly(meth)acrylate impact modifier comprising at least one multiphase alkyl(meth)acrylate emulsion polymer, comprising the following steps:
[0122] (i) preparing at least one heterogeneous alkyl (meth)acrylate emulsion polymer by emulsion polymerization, in particular by sequential emulsion polymerization, wherein the heterogeneous alkyl (meth)acrylate emulsion polymer is obtained in the form of a latex;
[0123] (ii) removing cations and optionally anions in an ion exchange step, wherein the latex obtained in step (i) is contacted with an ion exchange material, preferably a cation exchange material, more preferably a cation exchange material in protonated form;
[0124] (iii) coagulation and dehydration, preferably mechanical dehydration, of the latex obtained in step (ii), wherein the coagulation is carried out by means of physical coagulation, wherein a dehydrated alkyl (meth)acrylate emulsion polymer is obtained, and wherein the dehydrated alkyl (meth)acrylate emulsion polymer comprises less than or equal to 4.5 mmol / kg, preferably less than or equal to 3.0 mmol / kg, more preferably less than or equal to 2.0 mmol / kg, even more preferably less than or equal to 1.0 mmol / kg of alkali metal ions, such as sodium and / or potassium, based on the solid content of the impact modifier.
[0125] The preferred embodiments as described above in connection with the impact modifier of the invention apply correspondingly to the method of the invention.
[0126] In particular, the dehydrated alkyl (meth)acrylate emulsion polymer obtained in step (iii) comprises less than or equal to 20.0 mmol / kg, preferably less than or equal to 10.0 mmol / kg, more preferably less than or equal to 9.0 mmol / kg of cationic metal ions, based on the solid content of the impact modifier.
[0127] In particular, the poly(meth)acrylate impact modifier comprising or preferably consisting essentially of a heterogeneous alkyl(meth)acrylate emulsion polymer can be obtained as a dry polymer powder, in particular after dehydration and drying.
[0128] In particular, the poly(meth)acrylate impact modifier comprising or preferably consisting essentially of a multiphase alkyl(meth)acrylate emulsion polymer can be obtained in the form of polymer granules. For example, the polymer powder obtained after drying can be granulated, for example by means of generally known melt extrusion processes, optionally with the addition of one or more additives and / or one or more additional polymer components. Furthermore, it is possible to obtain the impact modifier in the form of polymer granules, wherein the coagulation and dehydration in step (ii) are carried out by means of thermal shear coagulation in an extruder.
[0129] In a preferred embodiment, the coagulation is carried out by means of freeze coagulation, wherein the aqueous phase of the coagulated emulsion polymer is at least partially removed by mechanical dehydration, for example in a centrifugation step. Typically, the water content of the dehydrated emulsion polymer is in the range of 5 to 40% by weight, preferably 7 to 30% by weight, based on the dehydrated emulsion polymer. In a preferred embodiment, the coagulation and dehydration in step (ii) are carried out as described in WO 2015 / 074883.
[0130] Preferably, step (ii) may comprise a sintering step as described below. Furthermore, the process of the present invention may comprise one or more washing steps (iii) and / or one or more drying steps (iv) as described below.
[0131] In a preferred embodiment, the coagulation and dehydration in step (ii) are carried out by extrusion. Typically, the latex obtained by emulsion polymerization is introduced into an extruder, which typically comprises a coagulation zone, a dehydration zone and a devolatilization zone. Preferably, the coagulation and dehydration by extrusion can be carried out as described in WO 02 / 18453, EP 0 683 028 or EP 0 187 715.
[0132] In another preferred embodiment, the coagulation and dehydration in step (ii) is carried out by freeze coagulation. Preferably, the coagulation and dehydration by freeze coagulation can be carried out as described in WO 2015 / 074883.
[0133] Emulsion polymerization step (i)
[0134] The process of the present invention comprises an emulsion polymerization step (i), wherein at least one heterogeneous alkyl (meth)acrylate polymer is prepared by emulsion polymerization, in particular by sequential emulsion polymerization, and the heterogeneous alkyl (meth)acrylate emulsion polymer is obtained in the form of a latex.
[0135] The multiphase emulsion polymers are prepared in the usual manner by two-stage, three-stage or multistage emulsion polymerization in aqueous phase. Typically, each stage of the emulsion polymerization is carried out at a temperature of from 20 to 100°C, preferably from 60 to 90°C.
[0136] Typically, the core is produced in the first stage by emulsion polymerization. Typically, the average particle size of the core is 50 to 150 nanometers (nm) for core-shell emulsion polymers and 100 to 300 nanometers (nm) for core-shell-shell emulsion polymers. Methods for adjusting the desired particle size are known to those skilled in the art. Advantageously, the particle size is controlled according to the seed latex method described in, for example, US 2007 / 0123610 A1 and WO 2004 / 056893.
[0137] In the case of core-shell emulsion polymers, the hard outer phase is produced in a second polymerization stage after completion of the first polymerization stage in the presence of a soft core.
[0138] In the case of core-shell-shell emulsion polymers, the elastomeric mesophase is prepared in a second polymerization stage after the first polymerization stage in the presence of the core. Finally, in a third stage, after the second polymerization stage, the final rigid phase is produced in the same manner in the presence of the emulsion polymer of the second stage.
[0139] The emulsion polymerization is suitably carried out in the presence of an anionic emulsifier. Commonly known anionic emulsifiers are, for example, alkyl sulfates, alkyl sulfonates, alkyl sulfonic acids, aralkyl sulfonates, soaps of saturated or unsaturated fatty acids. Anionic emulsifiers selected from sulfonates, alkyl sulfosuccinates and alkoxylated and sulfated paraffins and mixtures thereof are preferably used.
[0140] Preferably, the emulsion polymer latex is polymerized by aqueous free radical emulsion polymerization. The reaction is usually initiated by a water-soluble or oil-soluble free radical polymerization initiator.
[0141] For example, suitable polymerization initiators are selected from inorganic or organic peroxides, such as dilauroyl peroxide, tert-butyl peroctanoate, tert-butyl perisononanoate, dicyclohexyl peroxydicarbonate, dibenzoyl peroxide and 2,2-bis(tert-butylperoxy)butane; azo compounds, such as 2,2'-azobis(isobutyronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile), and redox initiator systems. Examples of suitable redox systems are combinations of tertiary amines with peroxides or sodium metabisulfite and potassium, sodium or ammonium persulfates or preferably peroxides.
[0142] It is also preferred to carry out the polymerization using a mixture of various polymerization initiators of different half-lives (eg, dilauroyl peroxide and 2,2-bis(tert-butylperoxy)butane) to keep the flux of free radicals constant during the polymerization or at various polymerization temperatures.
[0143] The polymerization initiator is generally used in an amount of 0.01 to 2% by weight, based on the monomer mixture. Typically, the polymerization initiator is used in the range of 0.01 to 0.5% by weight, based on the aqueous emulsion polymerization mixture.
[0144] Preferably, alkali metal peroxodisulfate or ammonium peroxodisulfate is used as polymerization initiator, for example in amounts of 0.01 to 0.5% by weight, based on the aqueous phase of the polymerization mixture, wherein the polymerization is preferably initiated at temperatures of 20 to 100°C.
[0145] Preferably, redox systems are used as polymerization initiators, for example 0.01 to 0.05% by weight of an organic hydroperoxide and 0.05 to 0.15% by weight of sodium hydroxymethanesulfinate (for example Rongalite®), each based on the aqueous phase of the polymerization mixture, wherein the polymerization is preferably initiated at temperatures of 20° C. to 80° C.
[0146] The chain length of the polymer can be adjusted, in particular in the external hard phase, by polymerizing the monomer mixture in the presence of a molecular weight regulator. In particular, known mercaptans can be used for this purpose, such as n-butyl mercaptan, n-dodecyl mercaptan, 2-mercaptoethanol or 2-ethylhexyl thioglycolate or pentaerythritol tetramercaptoacetate. Typically, the amount of the molecular weight regulator is 0.05 to 5 weight percent, based on the monomer mixture, preferably 0.1 to 2 weight percent, particularly preferably 0.2 to 1 weight percent, based on the monomer mixture. Preferably, n-dodecyl mercaptan is used as the molecular weight regulator.
[0147] It is also possible to use salts, acids and bases in the emulsion polymerization, in particular for adjusting the pH or buffering the reaction mixture. For example, solutions of sulfuric acid, phosphoric acid, sodium hydroxide, potassium hydroxide, carbonates, bicarbonates, sulfates and / or sodium and potassium salts of phosphates (e.g. tetrasodium pyrophosphate) may be used. Typically, the pH of the emulsion polymer latex obtained in step (i) is in the range of 2 to 7, preferably 2.5 to 6.
[0148] Typically, the solid content of the emulsion polymer latex obtained in step (i) is in the range of 20 to 60 wt %, based on the total weight of the emulsion polymer latex. If necessary, the solid content may be adjusted.
[0149] Ion exchange step (ii)
[0150] The method for producing an impact modifier according to the present invention comprises contacting the latex obtained in step (i) with an ion exchange material, preferably a cation exchange material, more preferably a strong acid cation exchange material, in particular in protonated form (H form). Preferably, after the ion exchange step, the amount of cationic metal ions is reduced to less than 1.0 mmol / kg. Thereafter, the latex is usually coagulated without adding ions (i.e. salts and / or acids), preferably without adding cations, such as alkali metal salts and alkaline earth metal salts.
[0151] Usually, the ion exchange material used in step (ii) can be at least one cation exchange material (i.e. material comprising anionic groups, which can be loaded with protons H+) and / or at least one amphoteric exchange material (i.e. material comprising anionic groups and cationic groups) and optionally at least one anion exchange material (i.e. material comprising cationic basic groups). Different ion exchange materials can be used as a mixture in a contact step with the emulsion polymer latex and / or used successively in two or more contact steps with the emulsion polymer latex. For example, it is possible to contact the latex obtained in step (i) with an anion exchange material in the first step, and then contact the latex with a cation exchange material in the second step. In addition, it is possible to use a mixed ion exchange material comprising anionic and cationic exchange groups.
[0152] Preferably, in case the emulsion polymerization in step (i) is carried out in the presence of anionic surfactants, at least one cation exchange material is used, more preferably as the only ion exchange material.
[0153] In order to avoid the coagulation of latex and the clogging of ion exchange material, nonionic surfactant can be added in ion exchange step (ii). In a preferred embodiment, at least one nonionic surfactant is added to latex before and / or during ion exchange step (ii). In particular, if anion stabilized latex (i.e., latex prepared by emulsion polymerization using anionic surfactant) is contacted with anion exchange material, coagulation of latex may occur. Suitable nonionic surfactants are, for example, alkylaryl polyethoxy alcohols and alkyl polyethoxy alcohols, such as octylphenol-ethoxylate (oxethylate) (TRITON® X 100, Rohm & Haas) or fatty alcohol (GENAPOL X 080, Clariant GmbH). Typically, nonionic surfactants are added in an amount of 0.001 to 3.0% by weight based on the solid content of the emulsion polymer latex. Such ion exchange steps are, for example, described in WO 2001 / 57100 A1, WO 99 / 62830 A and WO 99 / 62858 A.
[0154] In a preferred embodiment, the latex obtained in step (i) is contacted with at least one cation exchange material, more preferably a strong acid cation exchange material, in particular in protonated form (H form) in step (ii). Suitable cation exchange materials contain at least one acidic group, such as a carboxylic acid group (-COOH) or a sulfonic acid group (-S(=O)2OH), preferably a strong acid group, such as a sulfonic acid group. In the case where the cation exchange material is not in protonated form, for example in Na form, the cation exchange material can be treated with an aqueous acid solution, such as hydrochloric acid or sulfuric acid, to obtain the protonated H form of the exchange material. Suitable examples of commercially available cation exchange materials are those manufactured by Dow Chemical Co. under the trade names / trademarks DOWEX® MARATHONC, DOWEX® MONOSPHERE C-350, DOWEX® HCR-S / S, DOWEX® MARATHON MSC, DOWEX® MONOSPHERE 650C, DOWEX® HCR-W2, DOWEX® MSC-1, DOWEX® HGR NG (H), DOWEX® DR-G8, DOWEX® 88, DOWEX® MONOSPHERE 88, DOWEX® MONOSPHERE C-600 B, DOWEX® MONOSPHERE M-31, DOWEX® MONOSPHERE DR-2030, DOWEX® M-31, DOWEX® G-26 (H), DOWEX® 50W-X4, DOWEX® 50W-X8, DOWEX® ion exchange resins manufactured by Rohmand Haas under the trade names / trademarks Amberlyst® 131, Amberlyst® 15, Amberlyst® 16, Amberlyst® 31, Amberlyst® 33, Amberlyst® 35, Amberlyst® 36, Amberlyst® 39, Amberlyst® 40Amberlyst® 70, Amberlite® FPC11, Amberlite® FPC22, Amberlite® FPC23; ion exchange resins manufactured by Brotech Corp. under the trade names / trademarks Purofine® PFC150, Purolite® C145, Purolite® C150, Purolite® C160, Purofine® PFC100, Purolite® C100; and ion exchange resins manufactured by Thermax Limited Corp. under the trade names / trademarks Monoplus™ S100 and Tulsion® T42 ion exchange resins.Other acidic cation exchange resins known to those skilled in the art may also be used. Preferably, Dowex® Marathon C from Dow Chemical is used.
[0155] Furthermore, it is possible, preferably in addition to contacting the latex with a cation exchange material, to contact the latex obtained in step (i) with at least one anion exchange material. In this way, it is generally possible to reduce the amount of anions, for example sulphur-containing anions, to below 6.5 mmol / kg (calculated as sulphate). Preferably, if an anion exchange material is used and if an anion-stabilised emulsion polymer latex is used, at least one nonionic surfactant is added before and / or during step (ii).
[0156] Typically, weakly basic, moderately basic and strongly basic anion exchange materials can be used. Typically, the basic group can be selected from primary amino groups (-NH2), secondary amino groups (-NHR) and tertiary amino groups (-NR2), wherein the basic capacity increases from weak to moderate in this order. Typically, the functional groups of the anion exchange material can be selected from quaternary ammonium groups (also called Quat). Suitable anion exchange materials contain at least one functional cationic group, such as a trimethylamine group, a trimethylbenzylammonium group or a quaternary ammonium. In the case where the anion exchange material is not loaded with hydroxyl ions (i.e., Cl- form), the anion exchange material can be treated with an alkaline aqueous solution, such as sodium hydroxide solution or potassium hydroxide solution, to obtain a deprotonated form (OH- form) of the exchange material. A suitable example of a commercially available anion exchange material is DOWEX ® Resins of the 1X2, 1X4 and 1X8 series (Dow Chemical), AMBERLITE IRA 402, OAMBERJET 4200 (Rohm and Haas), OPUROLITE A 845 (Purolite GmbH), LEWATIT MP-500 (Bayer AG) type resins.
[0157] In step (ii), the latex obtained in step (i) is contacted with the at least one ion exchange material in any suitable manner. For example, the ion exchange step (ii) can be performed by dispersing the ion exchange material in the latex or in a column ion exchange step.
[0158] According to one embodiment, the ion exchange step (ii) can be carried out as a batch process by adding the ion exchange material to the latex in a stirred vessel and stirring the dispersion. After this treatment, the ion exchange material is typically removed from the latex, for example by filtration.
[0159] According to another embodiment, the ion exchange step (ii) is carried out as a column ion exchange process, preferably continuously. Typically, in the embodiment, the latex obtained in step (i) is passed through a column filled with an ion exchange material. Typically, the latex can be passed through the column by any means known in the chromatographic procedure, such as gravity feed, static siphon or automatic pumping system. Typically, the elution rate is 2 to 10 times (sometimes up to 46 times) of the bed volume per hour. Typical mass flow rates are 1.0 to 10 g / min.
[0160] Preferably, the ion exchange step (ii) is carried out using a latex obtained in step (i) having a solids content in the range of 20 to 60 wt.-%, based on the total weight of the latex, and / or having a pH value in the range of 2 to 7, preferably 2.5 to 6. If necessary, before the ion exchange step, the solids content of the latex obtained in step (i) may be reduced to 10 to 30 wt.-%, preferably to less than 20 wt.-%, in particular in order to avoid coagulation of the latex. If necessary, depending on the selected ion exchange material, it is possible to adjust the pH value before the ion exchange step.
[0161] Coagulation and mechanical dehydration step (iii)
[0162] The process of the present invention comprises coagulation and dehydration in step (iii), preferably mechanical dehydration, wherein the latex obtained in step (ii) is coagulated by means of physical coagulation, preferably selected from shear coagulation, hot shear coagulation, spray drying, freeze coagulation and pressure coagulation, more preferably by means of freeze coagulation, shear coagulation or hot shear coagulation, and wherein a dehydrated (meth)acrylate emulsion polymer is obtained, which contains less than or equal to 4.5 mmol / kg, preferably less than or equal to 3.0 mmol / kg, more preferably less than or equal to 1.0 mmol / kg of alkali metal ions based on the solid content of the (meth)acrylate emulsion polymer.
[0163] According to the present invention, "coagulation by physical means" or "physical coagulation" refers to agglomeration and precipitation of polymer particles in an emulsion polymer latex by applying physical methods, wherein the repulsive forces between the polymer particles are generally reduced, which achieves separation and stabilization of the polymer particles in the latex. Whereas "chemical coagulation" refers to agglomeration and precipitation of polymer particles in an emulsion polymer latex by adding chemical agents (coagulants), which generally achieve partial or complete neutralization of the stabilizing charges located at the polymer particles.
[0164] According to the process of the invention for producing poly(meth)acrylate impact modifiers, the coagulation is carried out by means of physical coagulation. Furthermore, it may be advantageous to add at least one coagulant, for example a salt of a polyvalent metal ion, before and / or during the coagulation.
[0165] Coagulation can also be performed without the addition of ionic species, preferably without the addition of cationic metal ions.
[0166] Physical coagulation of the emulsion polymer latex can be carried out by spray drying, freeze coagulation (described, for example, in WO 2015 / 07488) or by applying mechanical and / or thermal stress, in particular using a degassing extruder (described, for example, in WO 2002 / 18453, EP-A 0 979 162, EP-A 0 683 028).
[0167] Typically, the pH value of the coagulation mixture during the coagulation step (iii) is in the range of 3 to 8, preferably 2 to 7, more preferably 3 to 5, still more preferably 2 to 4.
[0168] It is possible to add at least one salt of a polyvalent metal ion (preferably selected from alkaline earth metals, zinc and aluminum) as a coagulant in the coagulation step (iii). For example, suitable alkaline earth metal salts here are magnesium sulfate (such as kieserite (Mg[SO4] • H2O), Epsom salt pentahydrate (Mg[SO4] • 5H2O), Epsom salt hexahydrate (Mg[SO4] • 6H2O) and Epsom salt (Mg[SO4] • 7H2O, Epsom salt)), magnesium chloride, calcium chloride, calcium hydroxide, calcium acetate, calcium formate, magnesium formate or mixtures thereof. For example, suitable aluminum salts are aluminum sulfate (Al2(SO4)3), aluminum sulfate hydrate, aluminum chloride (AlCl3), aluminum chloride hydrate, aluminum chlorohydrate and polyaluminum chloride. For example, suitable zinc salts are zinc chloride (ZnCl2), zinc sulfate (ZnSO4), zinc sulfate hydrate (e.g. ZnSO4 • 7H2O) and zinc oxalate.
[0169] The dehydration of the coagulated latex can be carried out by mechanical dehydration (e.g. centrifugation and / or filtration) and / or by thermal dehydration (e.g. by evaporation of the aqueous phase of the emulsion polymer, e.g. via spray drying). In addition, it is possible to carry out the coagulation and dehydration of the emulsion polymer latex in one step, e.g. in the case of spray drying or in the case of coagulation and dehydration in a degassing extruder.
[0170] Preferably, the dehydration of the coagulated emulsion polymer is carried out by mechanical dehydration, for example by means of centrifugation, decantation or filtration. Preferably, the coagulated emulsion polymer is dehydrated by means of batch or continuous centrifugation. Typically the coagulated emulsion polymer is centrifuged for a period of 90 seconds to 10 minutes.
[0171] According to a further embodiment of the invention, the dewatering of the coagulated emulsion polymer is carried out by means of a degassing extruder, in particular in at least one dewatering zone of an extruder for shear or hot shear coagulation of emulsion polymers.
[0172] Typically, the dewatered emulsion polymer obtained in step (iii) has a water content less than or equal to 40% by weight, preferably in the range of 2 to 35% by weight, more preferably 5 to 20% by weight.
[0173] The water content of the multistage emulsion polymer after dewatering (also called residual moisture content) is the water content expressed as percent by weight, based on the wet polymer obtained after dewatering. The water content is determined in particular with the aid of suitable analytical equipment, such as a drying and weighing device, wherein the sample is dried until a constant weight of the sample is achieved within a defined period of time. For example, the water content of the emulsion polymer can be determined in a moisture analyzer, wherein the sample is dried at a temperature of 80 to 180° C. In particular, the water content can be determined using a Halogen Moisture Analyzer from Mettler Toledo at 160° C. until a constant weight is achieved for 30 seconds.
[0174] Preferably, the dewatered alkyl (meth)acrylate emulsion polymer obtained in the dewatering step (iii) or after the optional washing step (iv) comprises less than or equal to 4.5 mmol / kg, preferably less than or equal to 3.0 mmol / kg, more preferably less than or equal to 1.0 mmol / kg of alkali metal ions (e.g. sodium and / or potassium), preferably less than or equal to 20.0 mmol / kg, preferably less than or equal to 10.0 mmol / kg of cationic metal ions, based on the solids content of the impact modifier, each based on the solids content of the emulsion polymer.
[0175] Optional sintering
[0176] In particular, step (iii) of the process of the present invention comprises a sintering step after coagulation of the emulsion polymer and before dehydration.
[0177] Preferably, step (iii) may comprise a sintering step, wherein the condensed multistage alkyl (meth)acrylate emulsion polymer may be maintained at a temperature close to or below the glass transition temperature T of the outer phase / shell of the multistage alkyl (meth)acrylate emulsion polymer. g The sintering temperature (T s ). Preferably, the optional sintering step is carried out after agglomeration and before dehydration. In particular, the optional sintering step is carried out at a temperature T s ≥T g - 50 K, preferably T s ≥T g - 30 K, preferably T g - 15K ≤ T s ≤T g +5 K.
[0178] Preferably, after the coagulation of the emulsion polymer, the coagulation mixture is kept at a temperature (sintering temperature) in the range of 60° C. to 140° C., preferably 70° C. to 135° C., more preferably 75° C. to 130° C. In particular, the coagulated emulsion polymer is kept at the sintering temperature T2 for a period of 2 minutes to 24 hours, preferably 2 to 15 minutes, preferably 3 to 10 minutes, more preferably 5 to 10 minutes.
[0179] In a preferred embodiment, the coagulated emulsion polymer may be treated with steam during a sintering step after coagulation.
[0180] In a preferred embodiment, the coagulated emulsion polymer may be diluted with water prior to the sintering step. For example, the volume of the coagulated emulsion polymer composition may be increased by 1.5 to 5 times, preferably 2 to 4 times, by adding water prior to sintering.
[0181] The method for producing the poly(meth)acrylate impact modifier may include one or both of the following optional steps:
[0182] (iv) optionally, washing of the dehydrated alkyl (meth)acrylate emulsion polymer;
[0183] (v) Optionally, drying of the dehydrated alkyl (meth)acrylate emulsion polymer obtained in step (iii) or (iv).
[0184] Optional washing step (iv)
[0185] In a preferred embodiment, the mechanical dehydration of the emulsion polymer in step (iii) is followed by a washing step (iv), wherein the dehydrated emulsion polymer is preferably treated with water or a mixture of water and a polar water-miscible organic solvent. The water or the mixture is preferably removed by filtration or centrifugation after this treatment. Preferably, in the downstream washing step (iv), an emulsion polymer having a water content of less than or equal to 40% by weight, preferably in the range of 2 to 35% by weight, more preferably in the range of 5 to 20% by weight, is obtained.
[0186] For example, the washing step (iv) may be performed by adding water or a mixture of water and a polar water-miscible organic solvent during centrifugation, in particular during continuous centrifugation.
[0187] Preferably, the dewatered emulsion polymer obtained after the optional washing step (iv) exhibits the amounts of alkali metal ions and polyvalent metal ions, such as alkaline earth metal ions, zinc ions or aluminium ions as described above for the dewatered emulsion polymer obtained after step (iii).
[0188] Optional drying step (v)
[0189] The process of the present invention for producing a poly(meth)acrylate impact modifier may comprise one or more optional drying steps (v).
[0190] For example, the dewatered emulsion polymer can be dried by means of a hot drying gas, for example air, or by means of a pneumatic dryer. Drying can be carried out, for example, in a cabinet dryer or other generally known drying apparatuses, such as a flash dryer or a fluidized bed dryer. Typically, the optional drying step (v) is carried out at a temperature of 50 to 160° C., preferably 55 to 155° C., particularly preferably 60 to 150° C.
[0191] In another embodiment, the coagulated and dewatered emulsion polymer is dried in a degassing extruder, in particular in an additional degassing section of the extruder used for coagulation and dewatering.
[0192] Typically, the resulting dried emulsion polymer has a water content of less than 5% by weight, preferably less than 2% by weight, preferably in the range from 0.05 to 2% by weight, preferably from 0.1 to 1.5% by weight, particularly preferably from 0.1 to 1% by weight.
[0193] Preferably, the dried emulsion polymer obtained, for example as powder or granules, exhibits the same amount of cationic metal salts, such as alkali metal ions and polyvalent metal ions, such as alkaline earth metal ions, zinc ions and aluminium ions, as the dewatered and optionally washed emulsion polymer obtained after step (iii) or (iv).
[0194] In a preferred embodiment of the present invention, in step (iii), the coagulation is carried out by means of freeze coagulation and the mechanical dehydration of the coagulated emulsion polymer is carried out by means of centrifugation, wherein the water content of the dehydrated emulsion polymer is less than or equal to 40% by weight, based on the dehydrated emulsion polymer, and wherein the method comprises
[0195] (iv) optionally, washing the dehydrated alkyl (meth)acrylate emulsion polymer;
[0196] (v) drying the dehydrated alkyl (meth)acrylate emulsion polymer obtained in step (iii) or (iv), wherein the poly (meth)acrylate impact modifier is obtained as a polymer powder.
[0197] According to another preferred embodiment of the present invention, in step (iii), coagulation and mechanical dehydration are carried out by means of thermal shear coagulation, wherein the latex obtained in step (ii) is introduced into an extruder line, which comprises at least one coagulation zone, at least one dehydration zone and at least one degassing zone, wherein the poly(meth)acrylate impact modifier is obtained as polymer particles.
[0198] Furthermore, the method for producing the poly(meth)acrylate impact modifier may include the optional steps of:
[0199] (vi) adding one or more additives to the multiphase alkyl (meth)acrylate emulsion polymer.
[0200] At each stage of the process for producing the poly(meth)acrylate impact modifier of the present invention, for example before or during the dehydration of the coagulated emulsion polymer, suitable conventional additives may be mixed in. These include dyes, pigments, stabilizers, lubricants, UV protectants, etc.
[0201] The optional additives can be selected from the commonly known additives and / or auxiliaries for plastic materials. For conventional auxiliaries and additives, reference is made, for example, to the "Plastics Additives Handbook", Hans Zweifel 6th edition, Hanser Publ., Munich, 2009. For example, the at least one additive can be selected from fillers, reinforcing agents, dyes, pigments, lubricants or mold release agents, stabilizers (especially light and heat stabilizers), antioxidants, UV absorbers, plasticizers, impact modifiers, antistatic agents, flame retardants, bactericides, fungicides, fluorescent whitening agents and foaming agents.
[0202] For example, the impact modifier may contain 0 to 15 wt %, preferably 0 to 10 wt %, more preferably 0.5 to 5 wt %, of at least one additive as described above, based on the solid content of the impact modifier.
[0203] Thermoplastic molding composition and method for producing the same
[0204] In another aspect, the present invention relates to a thermoplastic molding composition (hereinafter also referred to as molding composition), which comprises the poly(meth)acrylate impact modifier of the present invention and optionally at least one resin based on a thermoplastic (meth)acrylate polymer. For example, such an impact-modified poly(meth)acrylate molding composition is described in WO2004 / 056893.
[0205] In particular, the thermoplastic molding composition comprises (preferably consists of):
[0206] 1 to 100% by weight, preferably 5 to 100% by weight, based on the total molding composition, of at least one poly(meth)acrylate impact modifier as described above;
[0207] 0 to 99% by weight, preferably 0 to 95% by weight, based on the total molding composition, of at least one thermoplastic (meth)acrylate polymer, preferably at least one poly(methyl methacrylate), and
[0208] 0 to 50% by weight, preferably 0 to 10% by weight, based on the total molding composition, of one or more additives, preferably two or more additives, for example selected from UV absorbers, UV stabilizers, heat stabilizers, antioxidants, lubricants, dyes and processing agents; and / or one or more additional polymer components.
[0209] In general, the thermoplastic (meth)acrylate polymers here preferably comprise (preferably consist of), in each case based on their total weight,
[0210] 50.0 to 100.0% by weight, preferably 60.0 to 100.0% by weight, particularly preferably 75.0 to 100.0% by weight, in particular 85.0 to 99.5% by weight, of alkyl methacrylate monomers (or repeating units) having 1 to 20, preferably 1 to 12, more preferably 1 to 8, in particular 1 to 4 carbon atoms in the alkyl group,
[0211] 0.0 to 40.0% by weight, preferably 0.0 to 25.0% by weight, in particular 0.1 to 15.0% by weight of alkyl acrylate monomers (or repeating units) having 1 to 20, preferably 1 to 12, advantageously 1 to 8, in particular 1 to 4 carbon atoms in the alkyl group, and
[0212] 0.0 to 30 wt%, preferably 0.0 to 8.0 wt% of styrene monomers (or repeating units).
[0213] In particular, the thermoplastic (meth)acrylate polymer comprises at least 50.0% by weight, advantageously at least 60.0% by weight, preferably at least 75.0% by weight and in particular at least 85.0% by weight of methyl methacrylate, based on its total weight.
[0214] For example, the molding composition may comprise one or more additives selected from dyes, pigments and crosslinked polymer beads and / or one or more additional polymer components.
[0215] In a preferred embodiment, the thermoplastic molding composition of the invention as described above comprises up to 50% by weight, preferably 0.0001% to 50% by weight, based on the total thermoplastic molding composition, of at least one dye and / or pigment, for example selected from perinone dyes, quinophthalone dyes, anthraquinone dyes, azo dyes, inorganic pigments, phthalocyanine pigments and carbon black.
[0216] Furthermore, the thermoplastic molding composition of the invention as described above may contain 0.01% to 50% by weight, based on the total thermoplastic molding composition, of at least one crosslinked polymer bead, preferably selected from crosslinked polymer beads having a different refractive index compared to the refractive index of the polymer matrix formed by the thermoplastic molding composition (scattering beads). Suitable crosslinked polymer beads are described below.
[0217] Typically, the thermoplastic (meth)acrylate polymers have a number-average molar mass in the range of 1000 to 100 000 000 g / mol, preferably in the range of 10 000 to 1 000 000 g / mol, in particular in the range of 50 000 to 500 000 g / mol. The molar mass can be determined by gel permeation chromatography, for example with calibration based on polymethyl methacrylate.
[0218] The invention furthermore relates to a process for producing thermoplastic molding compositions, in which the components, usually in the form of their melt or in the form of powder or granules, are mixed and homogenized, for example in a single-screw or multi-screw extruder or on a roll mill.
[0219] In particular, the method for producing a thermoplastic molding composition comprises:
[0220] xi) mixing from 5 to 100% by weight, based on the total molding composition, of at least one poly(meth)acrylate impact modifier according to the invention as described above; from 0 to 95% by weight, based on the total molding composition, of at least one thermoplastic (meth)acrylate polymer; and optionally from 0 to 10% by weight of one or more additives and / or one or more additional polymer components; and
[0221] xii) melt compounding the mixture obtained in step xi) preferably at a temperature of 200 to 280°C.
[0222] Conventional additives can be mixed in at any processing stage suitable for this purpose. These include dyes, pigments, fillers, reinforcing fibers, lubricants, UV stabilizers, organic or inorganic scattering particles, etc.
[0223] Furthermore, the invention relates to mouldings or semi-finished products, such as foils, films or sheets, produced from the thermoplastic moulding compositions described above.
[0224] The thermoplastic molding composition can be used to produce any type of molded articles and semi-finished products, such as sheets, films, fiber foams, etc. The known thermoplastic processing methods can be used for processing, in particular, it can be produced by thermoforming, (co)extrusion, injection molding, calendering, blow molding, compression molding, press sintering, deep drawing or sintering, preferably by injection molding.
[0225] Molded products or semi-finished products
[0226] The invention also relates to a moulding or semi-finished product made from the thermoplastic moulding composition according to the invention as described above.
[0227] For example, the molded article or semi-finished product may comprise the thermoplastic molding composition of the invention as described above and further one or more additives as described above and / or one or more further polymer components, which additives may be selected from dyes, pigments and crosslinked polymer beads, for example.
[0228] Preferably, the molded article or semi-finished product comprises up to 50% by weight, preferably 0.0001% to 50% by weight, based on the total molded article or semi-finished product, of at least one additive, preferably selected from dyes, pigments, organic scattering particles (in particular crosslinked polymer beads as described below) and inorganic scattering particles.
[0229] Preferably, the molded article or semi-finished product comprises up to 50% by weight, preferably 0.0001% to 50% by weight, based on the total molded article or semi-finished product, of at least one dye and / or pigment, preferably selected from perinone dyes, quinophthalone dyes, anthraquinone dyes, azo dyes, inorganic pigments, phthalocyanine pigments and carbon black.
[0230] Preferably, the molded article or semi-finished product comprises from 0.01% to 50% by weight, based on the total molded article or semi-finished product, of at least one organic or inorganic scattering particle, preferably selected from crosslinked polymer beads, more preferably selected from crosslinked polymer beads having a refractive index different from the refractive index of the polymer matrix formed from the thermoplastic molding composition (scattering beads).
[0231] In a preferred embodiment, the semi-finished product is a film or a sheet.
[0232] In a preferred embodiment, the molded article or semi-finished product is transparent. In particular, the molded article or semi-finished product has a haze value of less than or equal to 30.0%, preferably less than or equal to 20.0%, more preferably less than or equal to 10%, in particular less than or equal to 6.0%, measured after storage in water at 80° C. for 4 hours to 24 hours, measured with the aid of a BYK Gardner Hazegard-plus haze meter according to ASTM D1003-13 at a material thickness of 40 μm-1000 μm. In particular, the molded article or semi-finished product has a haze value of less than or equal to 40.0%, preferably less than or equal to 30%, more preferably less than or equal to 25.0%, and also preferably less than or equal to 20.0%, measured after storage in water at 80° C. for 24 hours, measured according to standard ASTM D1003 (2013) at 23° C. on a specimen with a thickness of 1 mm.
[0233] In particular, the molded article or semi-finished product is produced by providing a thermoplastic molding composition as described above and adding at least one additive, in particular selected from dyes, pigments and crosslinked polymer beads as described above, and mixing the thermoplastic molding composition and the at least one additive, preferably by melt compounding, for example in the course of a film-forming process or an injection molding process.
[0234] Typically, the dyes and / or pigments can be added to the thermoplastic molding compositions of the invention as described above in the form of a coloring preparation, a liquid composition comprising the coloring preparation or a masterbatch.
[0235] In some embodiments of the present invention, the molding composition may contain organic or inorganic scattering particles dispersed in the polymer matrix. The low haze values of the impact-modified thermoplastic molding composition of the present invention after hot water storage may also be advantageous in combination with scattering particles, because even after hot water storage, a more uniform opaque and matte appearance can be obtained. Although the choice of scattering particles is not particularly limited, they are generally selected in such a way that the refractive index of the scattering particles differs from the refractive index of the copolymer matrix by at least 0.01. The refractive index can be measured at the Na D line at 589 nm at 23 ° C as specified in standard ISO 489 (1999).
[0236] The scattering particles typically have a weight-average particle diameter of 0.01 µm to 100.0 µm. The weight-average particle diameter of the scattering particles - expressed as the so-called volume-average d50-value (i.e. 50% by volume of the particles have a particle size below the specified average particle size) can be measured according to the laser diffraction measurement standard ISO 13320-1 (2009). Typically, the size of the scattering particles is determined by laser scattering at room temperature 23° C., for example, using a Beckman Coulter LS13 320 laser diffraction particle size analyzer.
[0237] Inorganic scattering particles may include conventional inorganic opacifiers such as barium sulfate, calcium carbonate, titanium dioxide, or zinc oxide.
[0238] The organic scattering particles are generally spherical scattering beads composed of crosslinked polymer materials such as polyalkyl (meth)acrylates, silicones, polystyrene, etc. Preferably, at least 70%, in particular at least 90%, of the scattering beads, based on the number of scattering beads, are spherical.
[0239] Preferred scattering beads composed of cross-linked polystyrene are commercially available from Sekisui Plastics Co., Ltd. under the trademarks Techpolymer® SBX-4, Techpolymer® SBX-6, Techpolymer® SBX-8 and Techpolymer® SBX-12.
[0240] Other particularly preferred spherical plastic particles for use as scattering agents include crosslinked silicones. Particularly preferred silicone scattering agents for use in the present invention are available as TOSPEARL® 120 and TOSPEARL® 3120 from Momentive Performance Materials Inc.
[0241] The present invention is described in more detail by the following examples and claims. DETAILED DESCRIPTION Example
[0242] Emulsion polymers EP1 (Examples 1-7) having a core-shell structure and emulsion polymers EP2 (Examples 8-9) and EP3 (Examples 10-12) having a core-shell-shell structure were prepared and freeze-coagulated. According to an embodiment of the present invention, the emulsion polymer latex was passed through an ion exchange material before freeze-coagulation.
[0243] I. Preparation of PMMA Latex Emulsion Polymer
[0244] Examples 1-6: Core-Shell Emulsion Polymer EP1
[0245] In a polymerization vessel equipped with a stirrer, a feed container and external cooling, an aqueous phase containing sodium hydroxymethyl sulfate, acetic acid, iron(II) sulfate (FeSO 4 ) and an aqueous solution of the seed latex (having a solid content of 5% by weight) was placed.
[0246] At a temperature of 55°C (container external temperature), emulsion I as described in Table 1 was added sequentially over a period of 20 minutes. After 10 minutes, emulsion II as described in Table 1 was added sequentially over 2 hours. The reaction mixture was stirred for 60 minutes, cooled to 45°C and filtered through VA steel (mesh size 90 μm). Emulsion I was obtained by emulsifying the monomers and components as shown in Table 1.
[0247] The amounts used are summarized in Table 1 below.
[0248] Table 1: Emulsion polymerization of latex emulsion polymer EP 1, all amounts are given in parts by weight
[0249] Hostapur® SAS 30 (Clariant): Sodium C14-17 alkyl secondary sulfonate
[0250] Irganox® 1076 (BASF): Sterically hindered phenolic antioxidant
[0251] The resulting aqueous polymer dispersion EP1 had a solids content of 40-42% by weight and an average particle diameter of about 124 nm, as determined by laser light scattering using a Beckman Coulter LS 13 320 laser diffraction particle size analyzer at room temperature 23°C.
[0252] Examples 7-9: Core-Shell-Shell Emulsion Polymer EP2
[0253] In a polymerization vessel equipped with a stirrer, a feed container and external cooling, an aqueous phase containing acetic acid, iron (II) sulfate (FeSO4) and seeds (containing 10% by weight of PMMA) was placed. At a temperature of 52°C (external temperature of the vessel), emulsion I as described in Table 2 was added over a period of 1 hour. In parallel, 0.69 g of sodium metabisulfite in 20 g of water were added (during the first 10 minutes).
[0254] After 15 minutes, in parallel with the start of the addition of emulsion II as described in Table 2, 1.94 parts by weight of sodium metabisulfite in 100 parts by weight of water were added over 10 minutes. Emulsion II (Table 2) was added over 2 hours, followed by a 50-minute interruption. Emulsion III as described in Table 2 was added simultaneously with 0.62 parts by weight of sodium metabisulfite in 50 parts by weight of water. The addition of sodium metabisulfite was completed over 10 minutes, emulsion III after 1 hour. Thereafter the reaction mixture was stirred for 30 minutes, cooled to 35° C. and filtered through VA-steel (mesh size 100 μm).
[0255] Emulsions I, II and III were each obtained by emulsifying the monomers and components shown in Table 2.
[0256] Table 2. Emulsion polymerization of latex emulsion polymer EP2, all amounts are given in parts by weight
[0257] Aerosol OT 75: An aqueous solution of dioctyl sodium sulfosuccinate (75%).
[0258] The resulting aqueous polymer dispersion EP2 had a solids content of 46-48% by weight and an average particle diameter of about 340 nm, as determined by laser light scattering using a Beckman Coulter LS 13 320 laser diffraction particle size analyzer at room temperature 23°C.
[0259] Examples 10-12: Core-Shell-Shell Emulsion Polymer EP3
[0260] In a polymerization vessel equipped with a stirrer, a feed container and external cooling, water, sodium carbonate and seeds (containing 10% by weight of PMMA) were placed. At a temperature of 83°C (internal container temperature), emulsion I as described in Table 3 was added over a period of 90 minutes (addition 10 minutes, interruption 10 minutes, addition 80 minutes). After an interruption of 10 minutes, emulsion II as described in Table 3 was added. Emulsion II was added within 2 hours and then interrupted for 30-45 minutes. Emulsion III was added within 1 hour. Thereafter, the reaction mixture was stirred for 30 minutes, cooled to room temperature (approximately 30 minutes) and filtered through VA-steel (mesh size 100 μm).
[0261] Emulsions I, II and III were each obtained by emulsifying the monomers and components shown in Table 3.
[0262] Table 3. Emulsion polymerization of latex emulsion polymer EP3, all amounts are given in parts by weight
[0263] Aerosol OT 75: An aqueous solution of dioctyl sodium sulfosuccinate (75%).
[0264] The resulting aqueous polymer dispersion EP3 had a solids content of 49-51 wt. % and an average particle diameter of about 250 nm, as determined by laser light scattering using a Beckman Coulter LS 13 320 laser diffraction particle size analyzer at room temperature 23°C.
[0265] II. Ion Exchange
[0266] The aqueous polymer dispersions of Examples 3-6 (core-shell emulsion polymer EP1), Examples 8 and 9 (core-shell-shell emulsion polymer EP2), and Examples 11 and 12 (core-shell-shell emulsion polymer EP3) were subjected to an ion exchange step prior to coagulation as described below.
[0267] For Examples 3, 5, 6 and 9, a glass column with an internal diameter of 16 mm was filled with 25 mL of a strongly acidic cation exchanger (Dowex® Marathon C from Dow Chemical) provided in protonated form (H form). The free volume above the ion exchanger bed was then filled manually with the respective dispersion. The dispersion was subsequently pumped through the column from top to bottom at a mass flow rate of 3.7 g / min (Example 3); 2.5 g / min (Example 5); 2.4 g / min (Example 6) or 3.5-5 g / min (Example 9).
[0268] For Examples 4, 8 and 12, approximately 200 mL of a strongly acidic ion exchanger (Dowex® Marathon C from Dow Chemical) was filled in a glass column with an inner diameter of approximately 50 mm. The free volume above the ion exchanger bed was then filled manually with the respective dispersion. Subsequently, a slight nitrogen pressure was applied to force the dispersion through the column.
[0269] For Examples 5.1, 5.2 and 11, 1000 mL of a strongly acidic ion exchanger (Dowex Marathon C) were filled in a stainless steel column with an internal diameter of 107 mm. The free volume above the ion exchanger bed was then filled manually with the respective dispersion. Subsequently, the dispersion was pumped through the column from top to bottom at a mass flow rate of 285 g / min (Examples 5.1 and 5.2) or 230 - 240 g / min (Example 11).
[0270] The procedures for Examples 1-12 are summarized in Table 4.
[0271] Samples were taken regularly at the column outlet and analyzed for sodium content by AAS.
[0272] III. Freeze-condensation, sintering and dehydration
[0273] The aqueous polymer dispersions of Examples 1-10 and 12 (partly after ion exchange treatment) were frozen at -18°C for 24 hours. Thereafter the mixture was sintered at 80°C for 24 hours. The latex was cooled to room temperature and the particles were separated from the water by centrifugation at 1800 rpm. The centrifugation time was varied between 1.5 and 10 minutes to result in different residual water contents (w(H2O)) in the coagulated and dehydrated emulsion polymers. In Examples 4, 8 and 12, the polymer was separated from the water by vacuum filtration instead of centrifugation.
[0274] After centrifugation or filtration, the polymer was washed with deionized water and centrifuged or filtered again. This procedure was performed three times and the resulting polymer powder was dried at 50°C for approximately 16-48 hours to obtain a final water content of <1%. Test specimens with a thickness of 1 mm were prepared from the dried material as described below.
[0275] For Examples 5.1, 5.2 and 11, the outlet of the ion exchanger column (described above) was continuously fed into a continuous flake ice machine (HIGEL HEC400) and continuously frozen at a roller temperature of -20°C, a roller speed of 1.2 rpm, and a filling level of 140 mm. The resulting ice was subsequently transferred to a 5 L continuous stirred tank reactor (CSTR), mixed with 110 g / min water (ambient temperature); 150 g / min and steam (160°C), and continuously thawed at a temperature of 85°C-95°C. The output of the CSTR was collected and centrifuged in batches at 2800 rpm for 10 minutes. The resulting dehydrated polymer was then dried in an oven at 46°C for 96 hours (Examples 5.1 and 11) or 72 hours (Example 5.2).
[0276] The procedures for Examples 1-12 are summarized in Table 4.
[0277] The water content (w(H2O)) after centrifugation was determined using an electronic moisture analyzer (Sartorius MA45). The results are given in the table below.
[0278] The metal ion content (eg, sodium content, calcium content, and magnesium content) of the dewatered and dried impact modifiers (emulsion polymers) of Examples 1 to 12 was determined as described below. The results are summarized in the table below.
[0279] Table 4: Ion exchange step and coagulation step *Embodiments of the present invention
[0280] MC: Dowex Marathon C
[0281] nd Not determined
[0282] IV. Preparation of Molding Compositions and Test Specimens
[0283] A test specimen having a thickness of 1 mm and a diameter of 5 cm was prepared by hot-pressing the polymer powder EP1 according to Examples 1-6 obtained as described above.
[0284] The impact modifiers (polymer powders) according to Examples 7-12 (based on emulsion polymers EP2 and EP3) were blended with PMMA_1 (a copolymer of approximately 96 wt % methyl methacrylate (MMA) and 4 wt % methyl acrylate, with a weight average molecular weight of approximately Mw=110,000), wherein the amount of impact modifier (w IM) are given in the table below. The polymer blends were prepared in a Haake Rheomix 5000 at a temperature of 220-230 °C (30 rpm). The resulting melt was removed from the chamber and crushed with pliers. Test specimens 1 mm thick and 5 cm in diameter were prepared by hot pressing of the pellets.
[0285] Further, a 53 μm film was produced by extrusion. The haze and transmittance of the film were measured as described below.
[0286] V. Results
[0287] The haze values and transmittance of the test specimens (1 mm) and films (53 µm) were determined as described below. The results are summarized in the table below.
[0288] The water content in the emulsion polymer obtained after coagulation and dehydration is indicated as w(H2O). The amount of impact modifier (emulsion polymer) in the molding composition or in the test specimens for haze and transmittance is indicated as w(IM) given in % by weight. The amount of metal ions and sulfur (calculated as sulfate) in the impact modifier (dried emulsion polymer) is given in mmol / kg (impact modifier).
[0289] Tables 5-6 (Examples 1 to 6) contain the results for core-shell emulsion polymer EP1 partially processed by acidic ion exchanger, freeze coagulation and mechanical dehydration.
[0290] Tables 7-8 summarize the results for core-shell-shell emulsion polymers EP2 (Examples 7-9) and EP3 (Examples 10-12) partially processed by acidic ion exchanger, freeze coagulation and mechanical dehydration and subsequently blended with PMMA_1.
[0291] Table 5: Test results of Examples 1-6 / ion content, transmittance and haze (sample, 1 mm) *Embodiments of the present invention
[0292] According to Example 5.3 (see Table 5a), an aqueous solution of calcium acetate (CaAc2) (coagulant) was added to the emulsion polymer EP1 after the ion exchange step. Ion exchange, coagulation and dehydration were carried out as described for Example 5 (see Section III above). It has been shown that the haze after hot water storage can be further improved by adding a specific amount of calcium salt as coagulant.
[0293] Table 5a: Test results of Examples 1, 5 and 5.3 / ion content and haze (specimen, 1 mm) *Embodiments of the present invention
[0294] Table 6: Test results of Examples 1-6 / Transmittance and Haze (Film, 53 µm) *Embodiments of the present invention
[0295] Table 7: Test results of Examples 7-9 / ion content, transmittance and haze (sample, 1 mm) *Embodiments of the present invention
[0296] Table 8: Test results of Examples 10-12 / ion content, transmittance and haze (sample, 1 mm) *Embodiments of the present invention
[0297] It has been shown that an improved hot water storage stability with regard to haze values and also transmittance is obtained if the amount of metal ions, in particular sodium ions, is reduced to less than 4.5 mmol / kg, preferably to less than 1 mmol / kg.
[0298] VI. Test Methods
[0299] a. Hot water mist
[0300] The test specimens (obtained by hot pressing, having a thickness of 1 mm and a diameter of 5 cm) were stored in deionized water at 80° C. for 24 hours. The haze values were measured before and after the hot water storage using a haze meter BYK Gardner haze-gard i according to ASTM D1003-13.
[0301] These specimens prepared as described above were tested at 23°C using a BYK Gardner haze-gard i haze meter according to ASTM D1003-13 in the original state ("before haze") and after hot water storage in deionized water at 80°C for 24 hours. It should be noted that materials with haze values greater than 30% are considered "diffuse" according to ASTM D1003-13 and should be tested according to Practice for Goniometric Optical Scatter Measurements (E2387). Since the focus of the current study is on transparent materials with haze values less than 30%, haze values greater than 30% are reported for the purpose of illustrating the trend.
[0302] These haze values and the difference (haze / Δ) between the haze values before and after hot water storage (haze / 24 h - haze / 0 h) are summarized in the above table.
[0303] The transmittance (given in %) before and after hot water storage was determined accordingly in accordance with ASTM D1003-13.
[0304] b. Metal ion content
[0305] To determine the metal ion content (e.g. Na and Ca), microwave-assisted digestion of the dried emulsion polymer was performed with nitric acid. Thereafter the content of the relevant ions was determined by atomic absorption spectroscopy.
[0306] To determine the sulfate content of the modifier, the polymer was digested by the Wickbold method. Thereafter, the sulfur content was determined using ion chromatography and the final sulfate (SO4 2- ) content. The sulfur content m calculated as sulfate ion is given in the above table S .
[0307] c. Water content
[0308] If not defined otherwise, the water content (residual water) was determined using an electronic moisture analyzer (Sartorius MA45) heated to 85 °C.
Claims
1. A poly(meth)acrylate impact modifier comprising at least one multiphase alkyl(meth)acrylate emulsion polymer, wherein the total amount of alkali metal ions in the impact modifier is less than or equal to 4.5 mmol / kg, preferably less than or equal to 3.0 mmol / kg, more preferably less than or equal to 2.0 mmol / kg, and even more preferably less than or equal to 1.0 mmol / kg, based on the solid content of the impact modifier.
2. The poly(meth)acrylate impact modifier according to claim 1, characterized in that The poly(meth)acrylate impact modifier comprises less than or equal to 20.0 mmol / kg, preferably less than or equal to 10.0 mmol / kg, more preferably less than or equal to 9.0 mmol / kg of cationic metal ions based on the solid content of the impact modifier.
3. The poly(meth)acrylate impact modifier according to claim 1 or 2, characterized in that: The multiphase alkyl (meth)acrylate emulsion polymer is obtained by emulsion polymerization and comprises a core and at least one shell, preferably one or two shells.
4. The poly(meth)acrylate impact modifier according to any one of claims 1 to 3, characterized in that The multiphase alkyl (meth)acrylate emulsion polymer comprises: at least 10% by weight, preferably at least 20% by weight, of at least one C1-C10 alkyl methacrylate; 5 to 80% by weight, preferably 20 to 80% by weight, of at least one C1-C10 alkyl acrylate or at least one conjugated diene; 0 to 2 wt. %, preferably 0.1 to 2 wt. %, of at least one crosslinking monomer; 0 to 15 wt %, preferably 0.5 to 10 wt % of optional additional monomers, preferably vinyl aromatic monomers.
5. The poly(meth)acrylate impact modifier according to any one of claims 1 to 4, characterized in that The multiphase alkyl (meth)acrylate emulsion polymer is a core-shell emulsion polymer comprising: A1) 10 to 95% by weight, based on the total emulsion polymer, of a soft elastomeric core A1 having a glass transition temperature T below -10°C g , which is composed of the following substances: A1.1) 50 to 99.5% by weight, based on A1, of at least one acrylic acid C1-C 10 Alkyl ester, preferably n-butyl acrylate; A1.2) 0.5 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and A1.3) 0 to 10% by weight, based on A1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer; and B1) 5 to 90% by weight, based on the total emulsion polymer, of a hard shell B1 having a glass transition temperature T above 70° C. g , which is composed of the following substances: B1.1) 80 to 100% by weight, based on B1, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate, and B1.2) 0 to 20% by weight, based on B1, of at least one further ethylenically unsaturated, free-radically polymerizable monomer.
6. The poly(meth)acrylate impact modifier according to any one of claims 1 to 5, characterized in that The multiphase alkyl (meth)acrylate emulsion polymer is a core-shell-shell emulsion polymer comprising: A2) 5 to 40% by weight, based on the total emulsion polymer, of a hard non-elastomeric core A2 having a glass transition temperature T above 50° C. g , which is composed of the following substances: A2.1) 80 to 100% by weight, based on A2, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate; A2.2) 0 to 20% by weight, based on A2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer; and A2.3) 0 to 5% by weight, based on A1, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; B2) 20 to 75% by weight, based on the total emulsion polymer, of a soft elastomeric intermediate shell B2 having a glass transition temperature T below 0° C. g , which is composed of the following substances: B2.1) 45 to 99.5% by weight, based on B2, of at least one acrylic acid C1-C 10 Alkyl ester, preferably n-butyl acrylate; B2.2) 0.5 to 5% by weight, based on B2, of at least one crosslinking monomer having two or more ethylenically unsaturated groups; and B2.3) 0 to 50% by weight, based on B2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer, preferably a monomer having aromatic groups; and C2) 15 to 60% by weight, based on the total emulsion polymer, of a hard shell C2 having a glass transition temperature T above 50° C. g , which is composed of the following substances: C2.1) 80 to 100% by weight, preferably 90 to 100% by weight, based on C2, of at least one C1-C6 alkyl methacrylate, preferably methyl methacrylate; and C2.2) 0 to 20% by weight, preferably 0 to 10% by weight, based on C2, of at least one further ethylenically unsaturated, free-radically polymerizable monomer.
7. A process for producing a poly(meth)acrylate impact modifier comprising at least one multiphase alkyl(meth)acrylate emulsion polymer according to any one of claims 1 to 6, comprising the following steps: (i) preparing at least one multiphase alkyl (meth)acrylate emulsion polymer by emulsion polymerization, wherein the multiphase alkyl (meth)acrylate emulsion polymer is obtained in the form of a latex; (ii) removing cations and optionally anions in an ion exchange step, wherein the latex obtained in step (i) is contacted with an ion exchange material; (iii) coagulation and dehydration, preferably mechanical dehydration, of the latex obtained in step (ii), wherein the coagulation is carried out by means of physical coagulation, wherein a dehydrated alkyl (meth)acrylate emulsion polymer is obtained, and wherein the dehydrated alkyl (meth)acrylate emulsion polymer comprises less than or equal to 4.5 mmol / kg, preferably less than or equal to 3.0 mmol / kg, more preferably less than or equal to 2.0 mmol / kg, even more preferably less than or equal to 1.0 mmol / kg of alkali metal ions, based on the solid content of the impact modifier.
8. The method according to claim 7, characterized in that In the ion exchange step (ii) at least one cation exchange material and / or at least one amphoteric exchange material and optionally at least one anion exchange material are used.
9. The method according to any one of claims 7 or 8, characterized in that At least one nonionic surfactant, preferably selected from alkylarylpolyethoxy alcohols and alkylpolyethoxy alcohols, is added to the latex before and / or during the ion exchange step (ii).
10. The method according to any one of claims 7 to 9, characterized in that: In step (iii), the coagulation is carried out by means of freeze coagulation and the mechanical dehydration of the coagulated emulsion polymer is carried out by means of centrifugation, wherein the water content of the dehydrated emulsion polymer is in the range of 5 to 40% by weight, preferably 7 to 30% by weight, based on the dehydrated emulsion polymer, and wherein the process comprises (iv) optionally, washing the dehydrated alkyl (meth)acrylate emulsion polymer; (v) drying the dehydrated alkyl (meth)acrylate emulsion polymer obtained in step (iii) or (iv), wherein the poly (meth)acrylate impact modifier is obtained as a polymer powder.
11. The method according to any one of claims 7 to 10, characterized in that: In step (iii), the coagulation and the mechanical dehydration are carried out by means of thermal shear coagulation, wherein the latex obtained in step (ii) is introduced into an extruder line comprising at least one coagulation zone, at least one dehydration zone and at least one degassing zone, wherein the poly(meth)acrylate impact modifier is obtained as polymer particles.
12. A thermoplastic molding composition comprising: 1 to 100% by weight, preferably 5 to 100% by weight, based on the total molding composition, of at least one poly(meth)acrylate impact modifier according to any of claims 1 to 6; 0 to 99% by weight, preferably 0 to 95% by weight, based on the total molding composition, of at least one thermoplastic (meth)acrylate polymer, preferably at least one poly(methyl methacrylate), and 0 to 50% by weight, preferably 0 to 10% by weight, based on the total molding composition, of one or more additives and / or one or more additional polymer components.
13. A method for producing a thermoplastic molding composition according to claim 12, comprising: xi) mixing from 1 to 100% by weight, preferably from 5 to 100% by weight, based on the total thermoplastic molding composition, of at least one poly(meth)acrylate impact modifier according to any of claims 1 to 7; from 0 to 99% by weight, preferably from 0 to 95% by weight, based on the total thermoplastic molding composition, of at least one thermoplastic (meth)acrylate polymer; and optionally from 0 to 50% by weight, preferably from 0 to 10% by weight, of one or more additives and / or one or more additional polymer components; and xii) Melt compounding the mixture obtained in step xi).
14. A molded article or semi-finished product made from the thermoplastic molding composition according to claim 12.
15. The molded article or semi-finished product according to claim 14, characterized in that The molded article or semi-finished product comprises up to 50% by weight, preferably 0.0001% by weight to 50% by weight, based on the total molded article or semi-finished product, of at least one additive selected from dyes, pigments, organic scattering particles and inorganic scattering particles.
16. The molded article or semi-finished product according to claim 14 or 15, characterized in that The molded article or semi-finished product has a haze value determined after storage in water at 80° C. for 24 hours, measured at 23° C. on a test specimen with a thickness of 1 mm, of less than or equal to 40.0%, preferably less than or equal to 30%, more preferably less than or equal to 25.0%, and further preferably less than or equal to 20.0%.
Citation Information
Patent Citations
Plastic film comprising a transparent plastic and a mixture of UV stabilisers and UV absorbers, used for producing high-quality, permanently non-weathering coatings on substrate materials or on PVC film
DE102005062687A1
Clear, impact-resistant acrylate molding compound
DE3842796A1
Process for the production of epsilon-caprolactam by catalytic conversion of a cyclohexanone oxime
EP0010245A1
Insulated collector for an electronic power tube
EP0020253A1
Information transducing apparatus
EP0030260A1